Aggression in Children : Reasons and Remedies - Bhatia, Ranjana (JOURNAL OF INDIAN EDUCATION, 2011)
Children are the creation of God. They are born with all happiness and spread lot of joy all around. Some turn out to be very happy, satisfied, calm and balanced youngsters while others become hostile and problem children. As hostile youngsters, they cause lot of harm to themselves and to those around them. There are definite reasons for their hostile behaviour which is quite often due to the environmental reasons. Parents, teachers and other factors are included in the environment. Studies have shown that environment plays a major role in acquiring the aggressive traits by the children. Awareness about the causes of aggression and the ways to check as well as control will help in preventing, minimising as well as controlling aggression in children. “Children are sick of being called ‘the future’. They want to enjoy their childhoods, free of violence, now”